The Influence of Brand Image, UKT and Location on the 2020 Student's Decision to Choose Trunojoyo Madura University - Najib Mutamam; Hadi Purnomo (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
The purpose of this study was to see whether the brand image, UKT and location had an effect both partially and simultaneously on the decision of students of class 2020 who chose Trunojoyo Madura UniversityThis research uses quantitative methods. The population of this study were students of the 2020 class of Trunojoyo Madura University. The sampling technique used was proportional stratified random sampling. The analysis method used is multiple linear regression. The results of investigating research show that brand image partially influences the decisions of students of class 2020 who choose Trunojoyo Madura University. UKT does not have a partial effect on the decision of the 2020 class students to choose Trunojoyo Madura University. Location partially influences the decision of students of class 2020 to choose Trunojoyo Madura University. Brand image, UKT and location simultaneously influence the decision of students of class 2020 to choose Trunojoyo Madura University.